Toxicity testing of combustion aerosols at the air–liquid interface with a self-contained and easy-to-use exposure system. (June 2016) - Mülhopt, Sonja; Dilger, Marco; Diabaté, Silvia; Schlager, Christoph; Krebs, Tobias; Zimmermann, Ralf; Buters, Jeroen; Oeder, Sebastian; Wäscher, Thomas; Weiss, Carsten; Paur, Hanns-Rudolf
Abstract: In vitro toxicity testing of airborne particles usually takes place in multi-well plates, where the cells are exposed to a suspension of particles in cell culture medium. Due to the artefacts caused by particle collection and preparation of suspensions, the air–liquid interface (ALI) exposure is challenging this conventional exposure technique to become the method of choice. The ALI technique allows for direct sampling of an aerosol and exposure of cell cultures to airborne particles. At the same time, it reflects the physiological conditions in the lung to a greater extent. So far, the available ALI systems have mostly been laboratory set-ups of the single components. Here, we present a mobile and complete system providing all process technology required for cell exposure experiments at dynamic aerosol sources. The system is controlled by a human machine interface (HMI) with standard routines for experiments and internal testing to assure reproducibility. It also provides documentation of the exposure experiment regarding process parameters and measured doses. The performance of this system is evaluated using fluorescein-sodium dosimetry, which is also used to determine the factor of dose enhancement by optional electrostatic deposition. The application of the system is shown for two different technical aerosol sources: wood smoke particles emitted by a household log wood stove and emissions from a ship diesel engine. After exposure of lung cells, cytotoxicity and gene regulation on a genome-wide scale were analysed. Highlights: We present a fully automated air–liquid-interface exposure system. System characterisation shows a high reproducibility. Wood combustion aerosol causes cytotoxicity in human lung epithelial cells. Gene regulation caused by ship diesel emissions in human lung epithelial cells.